2006
DOI: 10.1007/s11157-006-9111-2
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and life: some biological strategies

Abstract: All biological processes of life on Earth experience varying degrees of pressure. Aquatic organisms living in the deep-sea, as well as chondrocytic cells of articular cartilage are exposed to hydrostatic pressures that rise up to several hundred times that of atmospheric pressure. In the case of marine larvae that disperse through the oceanic water column, pressure changes might be responsible for stress conditions during development, limiting colonisation capabilities. In a number of biological systems, life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 99 publications
(136 reference statements)
0
54
0
Order By: Relevance
“…The effects of pressure and temperature on biological systems are usually antagonistic; i.e. an increase in pressure has similar effects to a decrease in temperature, reducing kinetic energy and causing ordering of molecules (Pradillon and Gaill, 2007). Indeed, low temperatures are known to exacerbate the effects of pressure on shallow-water invertebrate fauna (e.g.…”
Section: Temperature and Pressure Effects On Rates Of Oxygen Consumptmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of pressure and temperature on biological systems are usually antagonistic; i.e. an increase in pressure has similar effects to a decrease in temperature, reducing kinetic energy and causing ordering of molecules (Pradillon and Gaill, 2007). Indeed, low temperatures are known to exacerbate the effects of pressure on shallow-water invertebrate fauna (e.g.…”
Section: Temperature and Pressure Effects On Rates Of Oxygen Consumptmentioning
confidence: 99%
“…Baro-physiological studies involving animals adapted to 0.1MPa (atmospheric pressure) have demonstrated the pressure sensitivity of enzyme activity, protein structure and plasma membrane fluidity (for reviews, see Somero, 1992;Pradillon and Gaill, 2007). Under pressure, enzyme reactions associated with an increased system volume during catalysis are inhibited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, all biological processes are affected by hydrostatic pressure to varying degrees (Pradillon and Gaill, 2007). In the marine environment it has been argued that all organisms have upper and lower bathymetric limits (Tyler and Young, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Since large numbers of biological communities were first discovered near hydrothermal vents (Lonsdale 1977), much interest has been focused on the effects of hydrostatic pressure on a variety of deep-sea organisms (Sakiyama & Ohwada 1998, Kaye & Baross 2004, Partridge et al 2006, Campanaro et al 2008. Many studies have shown that organisms retrieved from depths of 2000 to 3000 m or more do not survive under normal pressure (Gross & Jaenicke 1994, Pradillon et al 2004, Pradillon & Gaill 2007. The effect of hydrostatic pressure on non-deep-sea organisms has been examined as well (Castillo et al 2004, Black et al 2005, Abe 2007, Horikawa et al 2009).…”
Section: Introductionmentioning
confidence: 99%